2002
DOI: 10.1021/bi025555g
|View full text |Cite
|
Sign up to set email alerts
|

An Isotope-Edited FT-IR Study of a Symporter, the Lactose Permease

Abstract: The lactose permease of Escherichia coli transports protons and lactose across the plasma membrane and uses a transmembrane ion gradient as the energy source to drive the uphill accumulation of lactose. In this report, the effect of the electrochemical gradient on the permease has been studied. Bacteriorhodopsin was co-reconstituted with the lactose permease to provide a light-triggered electrochemical gradient. Reaction-induced Fourier transform infrared spectra were acquired, and bacteriorhodopsin contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…It has also recently been reported that the patchy distribution of some proteins normally present in the MCC is lost upon membrane depolarization (Grossmann et al, 2007). This depolarization might affect the conformation of the intrinsic membrane proteins (Patzlaff et al, 2002) and consequently their association with surrounding lipids and their ability to aggregate preferentially with other proteins.…”
Section: Discussionmentioning
confidence: 96%
“…It has also recently been reported that the patchy distribution of some proteins normally present in the MCC is lost upon membrane depolarization (Grossmann et al, 2007). This depolarization might affect the conformation of the intrinsic membrane proteins (Patzlaff et al, 2002) and consequently their association with surrounding lipids and their ability to aggregate preferentially with other proteins.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, illumination of bacteriorhodopsin was used to generate a proton gradient in the presence of co-reconstituted lactose permease (LacY), a proton coupled sugar transporter, and the resulting spectral changes were measured by IR difference spectroscopy. 764 With universal 13 C and 15 N labeling of LacY, it was possible to obtain double-difference spectra free from spectral contributions from BR, containing information about changes in LacY induced by the proton gradient.…”
Section: Use Of Natural and Unnatural Amino Acids As Local Probesmentioning
confidence: 99%
“…Excitonic model simulations and comparisons with the measured spectra enabled the authors to show conclusively that the peptide forms an anti-parallel b-sheet in the membrane, and that the spectra are modulated by the vibrational couplings both in individual strands and between them. Barry and co-workers [13 ], on the other hand, have analyzed a significantly larger protein: the lactose permease (LacY), which contains 417 amino acid residues. The authors performed a 'reaction-induced difference FTIR', in which a reaction is initiated by changing the sample conditions and the resulting difference in the FTIR spectra is recorded.…”
Section: Examplesmentioning
confidence: 99%
“…spectra of the influenza A M2 transmembrane domain (25 amino acids) reconstituted in lipid bilayers[23]. The spectra shown are of samples with no label (gray line), a single13 C 16 O label (dashed line) or a single 13 C 18 O label (black line). The location of the unlabeled and labeled peaks are shown.…”
mentioning
confidence: 99%